Human Dignity, The Common Good, And Solidarity: A Catholic Agenda For Dialogue With China (The Macau Ricci Institute Journal, 2023)
The modern way of life promotes individualism and a quest for happiness restrained only by a certain measure of tolerance or justice. It is characterized by a limited and minimalist morality. Everyday life demands personal decision making, responsible choices, and critical judgement. Since men and women remain social beings, the question of how to establish more and more authentic interpersonal relations constantly arises. Nowadays one of the most fundamental challenges in philosophy is the question of ethics, viz. constructing a theory of morals that could guide men and women in their everyday activities. The tradition from which Catholic Social Teaching emerges considered all of life as a Divine creation. Humanity’s exercise of free will primarily consisted in discovering what God was expecting from us, the basis of our decision-making being the Divine indicative (Fergusson 2004, 23-47). Such an assumption seems to be slowly disappearing together with a gradual break with tradition in contrast with a growing emphasis on humanity as a rational, free, and autonomous being with equal rights (Jamnik 2018). Thus, when making ethical decisions, men and women today stand at a crossroads. In what follows I will try to outline the economic consequences of this crossroads moment, highlighting the meaning for business ethics of basic principles enshrined in Catholic Social Teaching. These are meant to stimulate dialogue with China, by offering a glimpse at a Western tradition not dominated by modern perspectives celebrating individualism and ethical relativism.